2022
DOI: 10.1111/jfb.15240
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary perspectives on the ecological impacts of invasive freshwater fishes

Abstract: Introductions of non‐native freshwater fish continue to increase globally, although only a small proportion of these introductions will result in an invasion. These invasive populations can cause ecological impacts in the receiving ecosystem through processes including increased competition and predation pressure, genetic introgression and the transmission of non‐native pathogens. Definitions of ecological impact emphasize that shifts in the strength of these processes are insufficient for characterizing impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 132 publications
0
15
1
1
Order By: Relevance
“…Although empirical evidence showed that non-native fishes can have detrimental ecological impact for native fishes and communities as a result of trophic interactions (Cucherousset and Olden, 2011;Britton, 2023), co-occurrence with nonnative pumpkinseed in the present study revealed no significant impact on chub growth and relative condition. In fact, a significant increase in growth but reduced condition was observed in both species in case of co-occurrence.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Although empirical evidence showed that non-native fishes can have detrimental ecological impact for native fishes and communities as a result of trophic interactions (Cucherousset and Olden, 2011;Britton, 2023), co-occurrence with nonnative pumpkinseed in the present study revealed no significant impact on chub growth and relative condition. In fact, a significant increase in growth but reduced condition was observed in both species in case of co-occurrence.…”
Section: Discussioncontrasting
confidence: 80%
“…Detrimental impacts of non-native species on native species have been widely recognized and reported (Gozlan et al, 2010;Britton, 2023), mainly through processes such as increased predation and interspecific competition, but also through habitat modifications and interactions resulting in interference (Gozlan et al, 2010;Cucherousset and Olden, 2011;Almeida et al, 2014). In the literature, there is usually a bias to focus on the cases where high abundances of invaders occur, but this inherently results in high ecological impacts, which potentially overstates the ecological consequences of non-native species (Gozlan, 2008;Jackson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One species clearly highlighted as high‐risk by our native and global RR o and RR b metrics was C. auratus , which is consistent with its extensive invasion history in Germany, elsewhere in Europe and around the world. With impacts stemming from high feeding rates (Dickey et al, 2022), generalist diets (Monello & Wight, 2001; Richardson et al, 1995), disruptive foraging behaviour and genetic introgression with other Carassius species (Britton, 2022), there is evident need to curtail its risk through price or availability. Other highlighted species with extensive invasion histories that scored highly on at least one RR b and at least one RR o list include the fishes Ctenopharyngodon idella and Poecilia reticulata , and the snail Melanoides tuberculata .…”
Section: Discussionmentioning
confidence: 99%
“…Two talks at the symposium, and papers in the special issue, deserve special note. The first, by Rob Britton (Britton, 2023), summarizes the impacts of introducing non-native freshwater fishes and, as such, an authoritative contribution to the subject. The second, by Josefin Sundin (Sundin, 2023), provides a fascinating overview of the recent ocean acidification controversy, highlighting the proliferation of influential studies purporting to show the reversal of predator avoidance behavior in CO 2 -exposed coral reef fish, which have ultimately proven problematic to replicate, and providing an indispensable case study for transparency and replicability in scientific publishing.…”
mentioning
confidence: 99%